Revolutionizing education: Artificial intelligence empowered learning in higher education - Rahiman, Habeeb Ur; Kodikal, Rashmi (Cogent education, 2024)
Global businesses are actively embracing Industry 4.0 and digital transformation. Simultaneously, the education sector is leveraging digital tools to foster personalized learning and equity. Universities transcending borders and students becoming increasingly global have opened new frontiers through the use of artificial intelligence (AI)-based tools in education. Since the role of AI is inevitable in future education, current research aims to identify the level of awareness of faculty members on the applicability and adoption of artificial intelligence. The study also intended to discover how AI enhanced their learning experience and impacted the degree of work engagement of teachers in higher education. A cluster and multi-stage sampling method was employed to select 250 faculty members from QS (Quacquarelli Symonds) ranked institutions operating in hybrid education modes. Utilizing a quantitative research approach and a structural equation model, factors influencing AI adoption in this context were explored. The findings revealed that AI implementation led to the evolution of robust evaluation and assessment methods, resulting in heightened faculty engagement levels. The study identified that perceived risk, performance expectancy, and awareness play significant roles in influencing work engagement and the adoption of AI within the higher education system through mediating variables, specifically attitude, and behavior.